Human skin reactions towards bites of tropical bed bug, Cimex hemipterus F. (Hemiptera: Cimicidae): A preliminary case study - Abd Rahim, Abd Hafis; Zahran, Zulaikha; Ab Majid, Abdul Hafiz (Elsevier, 2016)
Objective: To observe the manifestation of skin reactions and determine the time for skin reactions from bites of tropical bed bug (Cimex hemipterus) to disappear on different body parts. Methods: Forearm, upper arm and shoulder were exposed to tropical bed bugs and the manifestations of skin reactions afterwards were observed up to 144 h. Results: Itches, wheals and lesions were recorded for the three body parts. Itches were felt for about 15 min for all body parts. The wheals were recorded up to an hour before it flattened, and lesions manifested right after that and lasted for several days. One individual of bed bug took the least time for the skin reaction to disappear while shoulder recorded the longest time for the skin reactions to disappear completely. Conclusions: Different body parts may produce different skin reactions and the time required for the skin reactions to disappear completely was also varied.